Development of a fractional order based MIMO controller for high dynamic engine testbeds. (November 2016) - Lanusse, Patrick; Gruel, Dominique Nelson; Lamara, Abderrahim; Lesobre, Antoine; Wang, Xiaoqing; Chamaillard, Yann; Oustaloup, Alain
Abstract: Testbed are used to tune and assess automotive engines. As more High Dynamic (HD) scenarios need to be simulated, the testbeds require Multi Input Multi Output (MIMO) and robust control systems. A cooperation involving a major testbed manufacturer and two university laboratories was therefore set up. This paper presents the Control-System Design (CSD) methodology developed from system identification to the design and assessment of the MIMO robust controller for a HD testbed coupled with a spark-ignition engine. It is specially highlighted how the entire process has been automated and simplified and how the fractional order based MIMO CRONE CSD has been parameterized to obtain the best performance. Experimental results show that the proposed fractional order based MIMO control system is able to improve robustness and decoupling. Highlights: High dynamic testbeds used to tune and assess automotive engines are studied. An experimental HD testbed is coupled with a spark-ignition engine. A dynamical model of the nonlinear and Multi Input Multi Output system is identified. MIMO robust controllers are designed with the fractional order CRONE methodology. A controller designed with a simplified methodology is able to provide robustness and decoupling.